Native Client: A Clever Alternative. - Wallach, Dan (Communications of the ACM, 2010)
An introduction is presented to the article "Native Client: A Sandbox for Portable, Untrusted x86 Native Code," by Bennet Yee, David Sehr, Gregoiy Dardyk, J. Bradley Chen, Robert Muth, Tavis Ormandy, Shiki Okasaka, Neha Narula, and Nicholas Fullagar, published elsewhere in the same issue.